Моніторинг та оптимізація витрат в процесі управління державними програмами та проектами - Павліха, Наталія Володимирівна; Кицюк, Ірина Василівна; Pavlikha, Nataliia V.; Kytsiuk, Iryna V. (Национальный технический университет "Харьковский политехнический институт", 2016)
Пропонується розглядати управління програмами та проектами як ефективний інструмент підвищення соціально-економічних показників розвитку країни, оволодіти яким повинні не лише представники бізнесових структур, а й, насамперед, представники державних органів влади. Зроблено висновки, що встановлення чіткого взаємозв'язку між усіма функціями процесу управління державними програмами та/або проектами, їх ефективне виконання забезпечить досягнення поставленої мети, отримання передбачуваних результатів та вигод, дозволить здійснити оптимізацію інвестиційних витрат.

Analysis of implementation of the most state programs or projects shows that contracting authorities (program coordinators) don't conduct a monitoring of the realization of relevant programs and projects. Successful implementation in practice of monitoring of realization of state programs and projects primarily depends on a clear understanding of the notion of "monitoring", it tasks and place in the system of management of state programs and projects. The authors note that monitoring in the system of management of state programs and projects, in the narrow sense, it is a modern kind of analysis of these programs implementation and evaluation of effectiveness of raising and use of investment funds; in a broad sense it is a formation (tracking, collection, and data processing) of integrated information system on the state of implementation of programs and / or projects and use of raised funds and the data in the system are constantly updated through continuous tracking. It is noted that the establishment of a clear relationship between all of the functions of a process of management of realization of state programs and projects effective their implementation will provide achieving of the goal and obtaining the anticipated results and benefits, and will allow making the optimization of investment costs.
Monitoring and optimization of costs in the process of management of state programs and projects
Keywords: державні програми; проекти; управління; моніторинг; оптимізація; інвестиційні витрати; state programs; projects; monitoring; optimization; investment costs; management